Underutilization of BRCA1/2 testing to guide breast cancer treatment: black and Hispanic women particularly at risk - Levy, Douglas E. (2011)
PURPOSE: Women with early-onset (age ≤40) breast cancer are at high risk of carrying deleterious mutations in the BRCA1/2 genes; genetic assessment is thus recommended. Knowledge of BRCA1/2 mutation status is useful in guiding treatment decisions. To date, there has been no national study of BRCA1/2 testing among newly diagnosed women. METHODS: We used administrative data (2004–2007) from a national sample of 14.4 million commercially-insured patients to identify newly-diagnosed, early-onset breast cancer cases among women ages 20–40 (n=1,474). Cox models assessed BRCA1/2 testing, adjusting for covariates and differential lengths of follow-up. RESULTS: Overall, 30% of women age ≤40 received BRCA1/2 testing. In adjusted analyses, women of Jewish ethnicity were significantly more likely to be tested (HR=2.83, 95% CI 1.52–5.28), while black women (HR=0.34, 95% 0.18–0.64) and Hispanic women (HR=0.52, 95% CI 0.33–0.81) were significantly less likely to be tested than non-Jewish white women. Those enrolled in an HMO (HR=0.73, 95% CI 0.54–0.99) were significantly less likely to receive BRCA1/2 testing than those POS insurance plans. Testing rates rose sharply for women diagnosed in 2007 compared to 2004. CONCLUSIONS: In this national sample of newly diagnosed breast cancer patients at high risk for BRCA1/2 mutations, genetic assessment was low, with marked racial differences in testing.